Pendampingan dalam Perencanaan Penanaman Bawang Merah pada Kelompok Tani Harapan Jaya Kelurahan Talang Keramat Kecamatan Talang Kelapa Kabupaten Banyuasin - Jovan Febriantoko; Bastani Sepindjung; Riana Mayasari (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2020)
Agriculture is the process of utilizing biological resources. One of the community groups that run agricultural activities is the Harapan Jaya Farmers Group. It is located on Jalan Kauman RT 15, RW 03, Talang Kramat Village, Talang Kelapa Regency, Banyuasin, South Sumatra, which was then called a partner in the Community Partnership Program. Based on the interviews, observations, data analysis and identification of problems with the partners, several major problems were found: low pH land, lack of agricultural equipment, partners’ lack of ability to understand the techniques of shallots cultivation, less attractive packaging, and the absence of promotion. The solution to these problems was by conducting pre-implementation socialization and discussion, seeding shallots, planting media preparation, liming and fertilizing, planting shallots, designing agricultural equipment and conducting product marketing training. The results are the partners have completely understood about the process of planting shallots both from seed and from shallots tuber seedlings. The partners are also able to understand the working mechanism of agricultural aids thus they are able to repair the damage of their simple tools. Partners who are relatively young are able to manage the web thus it is expected to simplify the marketing process. Increasing the partners’ ability can increase the partners’ independence both personally and in groups. Increasing the potential of the agriculture field, especially regarding the planting of shallots could erase the pessimistic view of planting shallots in marshy and low pH land.